2016
DOI: 10.1055/s-0042-100471
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low- vs. Moderate-Load Squat Training on Strength, Jump and Sprint Performance in Physically Active Women

Abstract: This study aimed to analyze the effects of resistance training (RT) load on neuromuscular performance. Twenty-seven physically active women were randomly distributed into 3 groups: a low-load group (LLG); a moderate-load group (MLG); and a control group (CG). The RT consisted of full squat exercise with a low load (40-60% 1RM, LLG) or a moderate load (65-80% 1RM, MLG). Sprint times (T10, T20, and T10-20), countermovement jump (CMJ), estimated one-repetition maximum (1RMest) and velocity attained against the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
3
12
0
Order By: Relevance
“…Since RT using different relative loads could lead to distinct neuromuscular adaptations, it appears that further research is needed to elucidate the adaptations brought about by RT programs that establish different VL limits against other commonly used load ranges. In this regard, although previous research 29,30 has shown no differences in strength gains when using different relative loads, it appears that moderate loads (50–70% 1RM) may constitute a more effective stimulus than heavy loads (>80% 1RM) for inducing increments in jumping and sprinting performance, 31–33 which could be more beneficial for improving performance in different sports modalities. Thus, the aim of the present study was to compare the effects of three RT programs in which medium loads (55–70% 1RM) and different VL limits (10%, 30%, and 45%) were used on changes in strength, physical performance (jumping and sprinting ability), and EMG variables.…”
Section: Introductionmentioning
confidence: 88%
“…Since RT using different relative loads could lead to distinct neuromuscular adaptations, it appears that further research is needed to elucidate the adaptations brought about by RT programs that establish different VL limits against other commonly used load ranges. In this regard, although previous research 29,30 has shown no differences in strength gains when using different relative loads, it appears that moderate loads (50–70% 1RM) may constitute a more effective stimulus than heavy loads (>80% 1RM) for inducing increments in jumping and sprinting performance, 31–33 which could be more beneficial for improving performance in different sports modalities. Thus, the aim of the present study was to compare the effects of three RT programs in which medium loads (55–70% 1RM) and different VL limits (10%, 30%, and 45%) were used on changes in strength, physical performance (jumping and sprinting ability), and EMG variables.…”
Section: Introductionmentioning
confidence: 88%
“…To the best of our knowledge, no study has examined this relationship in untrained individuals. Nevertheless, previous studies have reported that long-term resistance training increases sprint performance, potentially by enhancing the knee extensor strength, in recreationally active young individuals [ 52 , 53 ]. This population was the same population to non-sprinters recruited in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there are no “strength,” “speed,” “power,” or “transfer” exercises, but only exercises performed at different velocities that could improve maximal force application against any absolute load. The absolute velocities used and, particularly, the degree of fatigue incurred during each training set will induce different effects on the force–velocity relationship [ 23 , 24 , 32 , 33 ]. Figure 3 shows three real examples of specific changes experienced in the load–velocity relationship following different RT programs.…”
Section: The Concept Of Maximal Strengthmentioning
confidence: 99%
“…Consequently, the "power phase" and "maximum strength phase" should not be considered as different and independent phases. In addition, as already indicated, the applied training load, particularly the degree of fatigue incurred during the training session, may induce different effects on different zones of the force–velocity curve [ 23 , 24 , 32 , 33 ]. However, power output will necessarily be improved against a given absolute load if the applied force increases, regardless of the part of the curve in which the effect occurs.…”
Section: Programming Models In Resistance Trainingmentioning
confidence: 99%
See 1 more Smart Citation